Applying concepts of plant nutrition in the real-world: Designing vertical farming systems. (2nd January 2023) - Tan, Aik-Ling; Ng, Yong Sim; Koh, Jaime; Ong, Yann Shiou; Koh, Dominic
Abstract: This integrated STEM activity on the design of a vertical farming system has biology as the lead discipline and relates to the concept of photosynthesis. Students investigated the optimal design of vertical farms that will deliver appropriate amounts of water, sunlight and carbon dioxide to plants such that there will be optimal yield. Through design, testing and refinement of their design, students appreciate the connections between photosynthesis, food supply and design.